Crisis of governance - Appu, P. S.; Bhattacharya, P. (ed) (Kolkatta, 2009)
This book examines the ways in which governance enables the smooth running of these societies, companies and organizations, from sub-national to international levels, and how the setting up of structures or institutional arrangements can impact this.
Keywords: Governance